2021
DOI: 10.1101/2021.05.31.21257974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The incidence of delirium in an acute geriatric community hospital: an observational cohort feasibility study

Abstract: Background Delirium in hospitalised older adults is associated with negative health outcomes. Admission to an alternative care setting may lower the incidence of delirium. The Acute Geriatric Community Hospital (AGCH) was recently opened in the Netherlands and uses a multi-component non-pharmacological intervention strategy to prevent delirium. Objective To describe the incidence of delirium found in the AGCH and compare this incidence to a hospital control group found in literature. Design Prospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…When nurse practitioners and physician assistants at the AGCH provide the care of the ECP (and/or hospital geriatrician), the legal consequences of transferring responsibilities should be clear [34]. Fourth, nursing home organizations will need to adjust their operations, logistics, and billing to provide acute care 24/7 because patient turnover is higher at the AGCH (x̄ length of stay 10 days [27]) than at the STRC (x̄ 34 days [35]) or GR (x4 3 days [36]). Finally, those providing specialized services at intermediate care facilities should use the 13 re ned admission criteria to determine which of these services can be de ned as AGCH care.…”
Section: Re Ection On Ndingsmentioning
confidence: 99%
See 1 more Smart Citation
“…When nurse practitioners and physician assistants at the AGCH provide the care of the ECP (and/or hospital geriatrician), the legal consequences of transferring responsibilities should be clear [34]. Fourth, nursing home organizations will need to adjust their operations, logistics, and billing to provide acute care 24/7 because patient turnover is higher at the AGCH (x̄ length of stay 10 days [27]) than at the STRC (x̄ 34 days [35]) or GR (x4 3 days [36]). Finally, those providing specialized services at intermediate care facilities should use the 13 re ned admission criteria to determine which of these services can be de ned as AGCH care.…”
Section: Re Ection On Ndingsmentioning
confidence: 99%
“…A prospective controlled observational study showed that patients admitted to the AGCH had a lower risk of readmission or death within 90 days after discharge than patients admitted to the hospital [25]. Patient satisfaction was high [26] and incident rates for delirium were lower [27] compared with control groups. These ndings have motivated multiple stakeholders to scale up the model to other sites in "XXXX".…”
Section: Introductionmentioning
confidence: 99%